Rural place attachment in Hispano urban centers - Smith, Jeffrey S. (My University, 2012)
Continued rural to urban migration is helping to motivate cultural geographers to better understand the complexity of the urban structure. Interpreting patterns of gender, class, ethnicity, and commercialization have proven to be fertile research areas, yet little is understood of the links between rural and urban places. Despite intense feelings of loyalty to their rural villages, the 1940s witnessed Hispanos moving en masse to cities. By the 1950s, due to higher wages and secure employment, a majority were living in regional urban centers. The Hispano experience provides a valuable crucible to examine how the attachment urbanites have for rural places is manifested in various urban cultural expressions. Presenting examples garnered from the cities of Albuquerque, Española, and Santa Fe, New Mexico and Pueblo, Colorado, this article illustrates how painted murals, burial preferences, popular music, and irrigation ditches provide urban dwellers with a link to the rural village ideal. Understanding threads of rural culture that have been incorporated into the urban fabric leads to a clearer comprehension of the emotional attachment urbanites have for rural areas and a better appreciation of the complexity of the urban cultural environment.
Keywords: Rural villages; Urban place attachment; Hispanos; New Mexico; Colorado